Transplantasi dan donor organ dalam telaah pembahasan fiqih kontemporer - Hesa, Nazwa Ayu Permata Ayu Permata (Maliki Interdisciplinary Journal, 2026)
Organ transplantation is one of the major advances in modern medicine that aims to replace the function of damaged organs in order to save lives and improve the quality of life of patients. From an Islamic perspective, this practice is not only viewed from a medical standpoint, but also from moral, spiritual, and Sharia law aspects. Islam views the human body as a trust from Allah SWT that must be preserved and respected, so that transplantation is only permitted if it is done with the intention of helping others, without coercion, and not for commercial purposes. Based on the ijtihad of contemporary scholars, organ transplantation is permitted as long as it provides greater benefit and does not cause harm, in accordance with the principle of hifz al-nafs (preserving life). There are several types of transplants, namely autotransplantation, allotransplantation, and xenotransplantation, each with its own medical and ethical considerations. Although it has great benefits in saving lives, transplantation also has the potential to lead to abuses such as the buying and selling of organs. Therefore, its implementation must be supervised by medical, legal, and religious authorities to ensure it remains consistent with Islamic principles. Overall, organ transplantation is viewed as a tangible expression of humanitarian values, mutual aid, and social worship.